Mycoplasma genitalium Infections and Associated Antimicrobial Resistance in Canada, 1980–2023 - Angela Copete; Mariana Herrera; Camilo Suarez-Ariza; Zipporah Gitau; Maria Arango-Uribe; Rotem Keynan; Camila Oda; Ameeta E. Singh; Stuart Skinner; Cara Spence; Will Riaño; Lauren J. MacKenzie; et al. (Tropical Medicine and Infectious Disease)
Background: We aimed to describe trends in M. genitalium prevalence and associated resistance in Canada between 1980 and 2022. Methods: Ecological study and a scoping review. We collected publicly available data published by the governments of all Canadian provinces and territories. We also systematically searched PubMed, Medline, Embase, and grey literature using the keywords ‘M. genitalium’, ‘Canada’, and all provinces and territories. We reported M. genitalium prevalence, age, sex, gender, symptoms, coinfections, sample types used for diagnosis, and macrolide and fluoroquinolone resistance rates. Results: National or provincial surveillance systems for M. genitalium are absent. Eight studies reported the epidemiology of M. genitalium. The prevalence ranged between 3% in Quebec and 30.3% in Ontario. Half of the patients reported symptoms. The most collected sample for M. genitalium diagnosis was urine, followed by cervical and urethral swabs. Co-infection with Chlamydia trachomatis was reported in 3.3% to 16.4% of cases and with Neisseria gonorrhoeae in 0.0% to 24.0%. Macrolide resistance ranged between 25% and 82.1%, and fluoroquinolone resistance between 0.0% and 29.1%. Conclusions: M. genitalium prevalence and resistance rates varied by sex, gender, province, and specimen type. In the absence of routine surveillance, incomplete data hinders understanding the bacterium’s natural history, its impact on some key groups, and the tracking of antibiotic resistance.